Atenção ao paciente com estomia: um percurso cartográfico potencializando o processo de trabalho em enfermagem - Nascimento, Márcia Elaine Costa do (Universidade do Vale do Rio dos Sinos, 2016)
This thesis aims to present the work process produced from a cartographic study of the ostomized patient and the Nursing team in the hospital setting, from an implementation of an Educational assistance intervention, called local support. This proposal was based on the principles of integrality of health care and on the politics of Permanent Education in health. The method used in this thesis is the cartographic research, which allowed and guided the experience of significant meetings between the assistant actors and the users. This method contributes with the production of innovative knowledge by problematizing the care practice supported by a sensible listening of collective constructions. The written production is original since it was guided by affectations, reflections, and singular listening of the author in relation to clinical and academic experiences. This study reveals that the local support became an important element among member of the nursing team by engendering actions that promote a more qualified care in terms of technical-assistance and in the mobilization of more collaborative actions in work relations.
Keywords: Estomia; Equipe de enfermagem; Cuidados de enfermagem; Processo de trabalho; Ostomy; Nursing team; Nursing care; Work process; ACCNPQ::Ciências da Saúde::Enfermagem